SYZYGIUM TINOMBALUM (MYRTACEAE), A NEW SPECIES FROM CENTRAL SULAWESI, INDONESIA - Siti Sunarti (Reinwardtia, 2020)
SUNARTI, S. 2020. Syzygium tinombalum (Myrtaceae), a new species from Central Sulawesi, Indonesia. Reinwardtia 19(2): 87‒91. ‒‒ Syzygium tinombalum Sunarti spec. nov. proposed as a new species from Central Sulawesi. Syzygium balgooyi and S. schumannianum are considered as the most closely related to Syzygium tinombalum. A full description of this species is given.